2020
DOI: 10.3389/fcell.2020.00714
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA cMTO1 Promotes PTEN Expression Through Sponging miR-181b-5p in Liver Fibrosis

Abstract: Background: Circular RNAs (circRNAs) are considered as key regulators of cancer biology. Recently, cMTO1 (a circRNA derived from MTO1 gene, hsa_circ_0007874) has been demonstrated to act as a tumor suppressor in hepatocellular carcinoma (HCC). However, the roles of cMTO1 in liver fibrosis are largely unknown. Methods: Expressions and roles of cMTO1 were examined in vivo and in vitro during liver fibrosis. The interaction between microRNA-181b-5p (miR-181b-5p) and cMTO1 was analyzed by luciferase activity assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Non-coding RNAs have been manifested not to be the transcriptional noise, and but to be the important regulatory molecules ( Zhuang et al, 2015 ; Chen et al, 2016 , 2017 ; Li et al, 2016a , b ; Tran et al, 2020 ), and circRNAs are novel endogenous non-coding RNAs that have been identified as owing key regulatory roles in the cancer biology ( Ma et al, 2019 ; Di Agostino et al, 2020 ; Dong et al, 2020 ; Jin et al, 2020 ; Li and Wang, 2020 ; Liu et al, 2020 ; Ou et al, 2020 ; Zhang et al, 2020a ). circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Non-coding RNAs have been manifested not to be the transcriptional noise, and but to be the important regulatory molecules ( Zhuang et al, 2015 ; Chen et al, 2016 , 2017 ; Li et al, 2016a , b ; Tran et al, 2020 ), and circRNAs are novel endogenous non-coding RNAs that have been identified as owing key regulatory roles in the cancer biology ( Ma et al, 2019 ; Di Agostino et al, 2020 ; Dong et al, 2020 ; Jin et al, 2020 ; Li and Wang, 2020 ; Liu et al, 2020 ; Ou et al, 2020 ; Zhang et al, 2020a ). circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ).…”
Section: Discussionmentioning
confidence: 99%
“…circRNAs act as important roles in the development and progression of cancers and are involved in various biological processes, such as cell proliferation, apoptosis, and migration by regulating gene expression ( Liu et al, 2019 ; Di Agostino et al, 2020 ; Ji et al, 2020 ; Tang and Chen, 2020 ; Wang et al, 2020c ). Mangy circRNAs have been reported to play important functions in cervical cancers, such as hsa_circ_0000515 ( Tang and Chen, 2020 ), has_ circ_0000388 ( Meng et al, 2020 ), circ-HIPK3 ( Qian and Huang, 2020 ), circ-ITCH ( Li et al, 2020 ; Wu et al, 2020b ), circCLK3 ( Jin et al, 2020 ), etc. However, the role and mechanism of circAMOTL1 in the cervical cancer are thoroughly unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations